Harnessing Generative AI in Higher Education: Opportunities, Challenges, and Ethical Imperatives - Ravichandran, R.; Sasikala, P. (Journal of Digital Learning and Education, 2025)
Generative Artificial Intelligence (AI) is poised to transform higher education, particularly in complex and diverse contexts such as India. This article critically examines the potential of generative AI to address longstanding challenges, including the digital divide, the need for scalable personalized learning, and the evolving role of educators. It explores how AI tools can enhance student engagement, support teacher empowerment, and enable inclusive learning, especially in under-resourced settings. The paper also interrogates key ethical concerns, such as academic integrity, data privacy, algorithmic bias, and equity, while analysing current government initiatives aimed at responsible AI adoption. Drawing on global comparisons and field-based perspectives, the article presents a balanced analysis of both the opportunities and limitations of AI in Indian higher education. It concludes by offering practical recommendations for policy, pedagogy, and future research to foster a more equitable, AI-enabled academic ecosystem